PENGARUH VOLUME TRANSAKSI, RESIKO PASAR DAN DEBT TO EQUITY RATIO TERHADAP KEBIJAKAN DIVIDEN - Soelehan, Aan; Magdalena, Annaria; Loren, Tirza (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
This study was conducted to examine the effect of variable transaction volume, market risk and debt-to-equity ratio on the variable dividend policy. The study was conducted at five companies listed on the Stock Exchange in the period 2011-2013 per quarter. The method of research used a sample to the five companies listed on the Stock Exchange in the period 2011-2013. Data obtained by IDX publications 2011-2013. The analysis technique used is multiple regression and hypothesis testing using the t-statisticfor testing the partial regression coeficients and F-statistics for testing simultaneous regression coeficient with a significance level of 5%. From the results of the analysis showed that the volume of transactions pasial variables no significant effect on dividend policy. The results of the analysis of the risk variables significantly negative market partially on dividend policy. The results of the analysis of variable debt to equity ratio is partially significant negative effect on dividend policy. Keywords: transaction volume, market risk, debt to equity ratio and dividend policy.